Feux de végétation Comprendre leur diversité et leur évolution - Barbero, Renaud (éditions Quae, 2022)
Each year, the world burns an area of forest and natural vegetation equivalent to that of Europe. Climate, human activities and vegetation are the three main factors that control fires and sometimes modify their behaviour and even their danger. The danger is therefore increasing in certain "hot spots" around the world where most fires are concentrated, particularly with the development of mega-fires. However, the millennia-old history of fires in the world teaches us that fire is a natural process that is essential for the maintenance of many ecosystems and species. In many countries, it is also an ally in cultivating the land. The effects of fire can therefore be dramatic, but also beneficial. There is little literature on fire on a global scale. Aimed at decision-makers as well as a wider public, this book, illustrated with numerous examples, is a synthesis of current knowledge on the ecology of fire and its geography. It suggests that it is possible to live sustainably with fire provided that we adapt and manage landscapes intelligently, in order to reduce the risk of fire while preserving biodiversity.